\(\left(x^2-6x+9\right)+15\left(x^2-6x+10\right)=1\)
\(\Leftrightarrow\left(x-3\right)^2+15\left[\left(x-3\right)^2+1\right]=1\)
\(\Leftrightarrow16\left(x-3\right)^2+15=1\)
\(\Leftrightarrow16\left(x-3\right)^2=-14\)
=> Phương trình vô nghiệm
\(\left(x^2-6x+9\right)-15\left(x^2-6x+10\right)=1\)
Đặt : \(x^2-6x+9=\left(x-3\right)^2=t\) thay vào pt ta được :
\(t^2-15\left(t+1\right)=1\)
\(\Leftrightarrow t^2-15t-16=0\)
\(\Leftrightarrow\left(t+1\right)\left(t-16\right)=0\)
\(\Leftrightarrow t=\left\{{}\begin{matrix}16\\-1\end{matrix}\right.\)
với : \(t=-1\) thì \(\left(x-3\right)^2=-1\)
\(\Rightarrow ptvonghiem\)
Với : \(t=16\) thì \(\left(x-3\right)^2=16\)
\(\Leftrightarrow x\in\left\{{}\begin{matrix}7\\-1\end{matrix}\right.\)
\(vay...\)
thôi chết rồi em nhầm đáng lẽ là : \(\left(x^2-6x+9\right)^2\) á